Regulation of Public Finances in Poland in Light of Financial Constitutionality - Charkiewicz, Mariusz; Popławski, Mariusz (Regulation of Public Finances in Light of Financial Constitutionality: Analysis on Certain Central and Eastern European Countries, 2022)
This chapter deals with the notion, scope of public finance, and legal sources regulating this field. There are many difficulties in formulating a definition of finance law, which result from the diversity of the matter regulated by public finance. Financial law comprises many acts of law and accompanying executive acts. All these regulations define the rules of collecting and spending money for public purposes. The norms of financial law serve the purpose of realization of social and economic tasks of the state. The basis of this field of law is the Polish constitution. The aim of this article is to present areas of regulation, current problems, and challenges of the financial law, as well as to bring closer the constitutional regulations and principles relating to finance. General principles concerning economy in public finance constitute an important element of the socioeconomic system of a country. Hence, they should be, and are, properly regulated in the basic law. In the Polish Basic Law, public finance is directly addressed, first, in Chapter X, entitled ‘Public Finance’. However, it is also dealt with in other articles scattered in the remaining chapters. The issues of the state’s financial system are further regulated in Chapter VII—’Local government’ (art. 167, art. 171 par. 2, et al.); in Chapter VI—’The Council of Ministers and government Administration’ (Article 146, paragraph 2, items 5 and 6). In many places, the constitution also refers to concepts from the financial system, such as ‘financial outlays, not provided for in the Budget Act (art. 190 par. 3), or ‘financing of political parties, which is to be public’ (art. 11 par. 2). KEYWORDS: Financial law, tax law, budgetary law, customs law, public banking law, foreign exchange law, monetary law, social security system, constitution, financial principles, legal institutions.